Effects of various sweeteners on chemical composition of guava slices - Ayub, Mohammad; Zeb, Alam; Ullah, Javid; Khattak, Muhammad Muzaffar Ali Khan (Agricultural University, Peshawar, 2005)
This research was conducted in the Department of Food Science andTechnology NWFP Agricultural University, Peshawar, Pakistan during 2003-04 to know the effectiveness of sucrose, glucose, fructose and theirmixture along with chemical preservatives (potassium metabisulphite andpotassium sorbate) and anti oxidants (citric acid and ascorbic acid) onnutrients stability of intermediate moisture(IM) sweetened guava slices. Theguava slices after osmotic dehydration in these nutritive sweeteners (NS)were again cabinet dehydrated to final moisture content of 25%. The totalsoluble solids (TSS) of the slices increased from 10 degree to 38.24 degreebrix (bx) during osmotic dehydration in 20, 30, 40 and 50 degree bx inthese sweeteners respectively. Ascorbic acid content decreased from 293.9mg/100 g to 44.51 mg/100 g during dehydration. The pH of fresh guavaslices decreased from 4.00 to 3.77, while percent acidity increased from0.026 to 0.272 percent during osmotic dehydration. The sugar acid ratiodecreased from 390.6 to 182.0 and moisture content decreased from 85% to53.09% during osmotic dehydration. T19 sucrose/glucose (7:3), ascorbic acidand potassium metabisulphite and T17 (sucrose/glucose (7:3), citric acidand potassium metabisulphite were found to be the most effectivesweeteners combination in maintaining the nutrients stability of IM guavaslices.